2011
DOI: 10.3727/096368910x540621
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Induction of Myeloid Suppressor Cells and CD4+Foxp3+T Regulatory Cells Prolongs Skin Allograft Survival in Mice

Abstract: Natural CD4+ Foxp3 + T regulatory (Treg) cells can promote transplantation acceptance across major histocompatibility complex (MHC) barriers, while myeloid-derived suppressor cells (MDSCs) inhibit effector Tcell responses in tumor-bearing mice. One outstanding issue is whether combining the potent suppressive function of MDSCs with that of Treg cells might synergistically favor graft tolerance. In the present study, we evaluated the therapeutic potential of MDSCs and natural Treg cells in promoting allograft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 54 publications
2
53
0
1
Order By: Relevance
“…18 However, since the grafts comprised cell lines from a heterologous (mixed) genetic background, or from cells virally transduced to exogenously express foreign proteins, the antitumour activity of endogenous CD8 T cells in this setting was probably due, at least in part, to recognition of minor histocompatibility alloantigens or foreign epitopes. These findings are consistent with previous work demonstrating that myeloid-derived suppressor cells (MDSC) can prevent graft rejection, [19][20][21][22] but leave unaddressed the potential therapeutic benefit of this strategy in a clinical oncology setting. Furthermore, it remains unclear if disrupting cancer-associated myeloid cells would have an impact on established, autochthonous pancreas cancers.…”
Section: Significance Of This Studysupporting
confidence: 92%
“…18 However, since the grafts comprised cell lines from a heterologous (mixed) genetic background, or from cells virally transduced to exogenously express foreign proteins, the antitumour activity of endogenous CD8 T cells in this setting was probably due, at least in part, to recognition of minor histocompatibility alloantigens or foreign epitopes. These findings are consistent with previous work demonstrating that myeloid-derived suppressor cells (MDSC) can prevent graft rejection, [19][20][21][22] but leave unaddressed the potential therapeutic benefit of this strategy in a clinical oncology setting. Furthermore, it remains unclear if disrupting cancer-associated myeloid cells would have an impact on established, autochthonous pancreas cancers.…”
Section: Significance Of This Studysupporting
confidence: 92%
“…C Gr-1 C MDSCs from G-CSF-treated mice, 16 supporting the hypothesis that the systemic recruitment and trafficking result in increased frequencies at multiple peripheral sites. Movahedi et al presented …”
Section: The Phenotypes Of Mdscssupporting
confidence: 58%
“…43 The administration of recombinant G-CSF or IL-2 in mice results in the accumulation of Gr-1 C CD11b C MDSCs and Treg cells in the peripheral lymphoid organs, which significantly delays allogeneic donor skin rejection. 16 It was reported that IL-1R deficiency delays MDSC accumulation in tumorbearing mice. 44 In contrast, excessive inflammation in IL-1R antagonist-deficient mice promotes the accumulation of MDSCs with enhanced immunosuppressive activity.…”
Section: Inflammatory Cytokines and Growth Factorsmentioning
confidence: 99%
“…Indeed, transplant tolerance is mostly associated with the action of regulatory T cells (Treg) (14) working in synergy with MDSC (15,16) and other suppressive cell types, such as monocytes (17), NK cells (18), plasmacytoid dendritic cells (19)(20)(21)(22), or immature dendritic cells (23). However, the mechanisms involved in this cooperation are not well understood.…”
mentioning
confidence: 99%